1999
DOI: 10.3177/jnsv.45.567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a New Amino Acid Solution on Nutritional Status and Nitrogen Metabolism in Rats with Chronic Renal Failure Undergoing Hyperalimentation.

Abstract: SummaryWe studied the effects of the new amino acid solution MRX-III on the nutritional status and nitrogen metabolism of rats with chronic renal failure (CRF) in comparison with those of a general amino acid solution (MPR-F). The essential amino acids/non-essential amino acids ratio was 3.21 for MRX-III and 1.09 for MPR-F. Rats with CRF, induced by 7/8 renal ablation, were divided into 6 groups of 8 rats each receiving total parenteral nutrition (TPN) containing MRX-III or MPR-F at a non-protein calorie/nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
4
1
0
Order By: Relevance
“…The serial time points of the blood biochemistry results in the TPN group are similar to the MAN group and our background data from orally fed rats. The blood biochemistry results in this study were similar to reported data for TPN rats (Mochida et al, 1991;Yamauchi and Kokuba, 1999). Since Al-P, T-Cho, TG, TP and ALB of our background data performed overnight fasting before blood biochemistry examinations, it showed a low value as compared with the blood biochemistry results in this study, but they were small differences.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The serial time points of the blood biochemistry results in the TPN group are similar to the MAN group and our background data from orally fed rats. The blood biochemistry results in this study were similar to reported data for TPN rats (Mochida et al, 1991;Yamauchi and Kokuba, 1999). Since Al-P, T-Cho, TG, TP and ALB of our background data performed overnight fasting before blood biochemistry examinations, it showed a low value as compared with the blood biochemistry results in this study, but they were small differences.…”
Section: Discussionsupporting
confidence: 90%
“…Changes of all the blood biochemistry results in the TPN group showed results similar to MAN group. Blood biochemistry results in this study were within the limits of our background data, and were scientifically acceptable for TPN experiments (Mochida et al, 1991;Yamauchi and Kokuba, 1999). Although the overloading syndrome is reported to be a side effect in the early stages of TPN in rats (Silvis and Paragas, 1971), this syndrome is observed as increases in AST and ALT.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, no abnormality in this group was observed in the clinical signs. As shown in the blood biochemistry results (Tables 9 and 10), blood biochemistry results did not vary with MAN and TPN solution treatment rats, which is similar to the our background data in orally fed rats and TPN solution treatment rats (As anuma et al, 2006;M ochida et al, 1991;Yamauchi and Kokuba, 1999).…”
Section: Discussionsupporting
confidence: 74%
“…The blood biochemistry results did not vary with MAN and TPN solution treatment rats, which is similar to our background data in orally fed rats and TPN solution treatment rats (Asanuma et al, 2006;Mochida et al, 1991;Yamauchi and Kokuba, 1999).…”
Section: Blood Biochemistrysupporting
confidence: 78%